Sustainable maternity services in remote and rural Scotland? A qualitative survey of staff views on required skills, competencies and training. Issue 1 (3rd February 2005) - Tucker, J; Hundley, V; Kiger, A; Bryers, H; Caldow, J; Farmer, J; Harris, F; Ireland, J; van Teijlingen, E
Abstract : Objectives: To explore staff views on their roles, skills and training to deliver high quality and local intrapartum services in remote and rural settings against national recommendations. Design: Interview and postal survey. Setting: A stratified representative sample of remote and rural maternity units in Scotland (December 2002 to May 2003). Participants: Staff proportionally representative of professional groups involved in maternity care. Results: Staff interviews took place at 11 units (response rate 93%). A subsequent postal survey included the interview sample and staff in a further 11 units (response rate 78%). Medical specialisation, workforce issues, and proposed regulatory evaluation of competencies linked to throughput raised concerns about the sustainability and safety of services, particularly for "generalists" in rural maternity care teams and for medical cover in small district general hospitals with large rural catchments. Risk assessment and decision making to transfer were seen as central for effective rural practice and these were influenced by rural context. Staff self-reported competence and confidence varied according to procedure, but noted service change appeared to be underway ahead of their preparedness. Self-reported competence in managing obstetric emergencies was surprisingly high, with the caveat that they were not independently assessed in this study. Staff with access to video conference technology reported low actual use although there was enthusiasm about its potential use. Conclusions: Considerable uncertainties remain around staffing models and training to maintain maternity care team skills and competencies. Further research is required to test how this will impact on safety, appropriateness, and access and acceptability to rural communities.